Effect of Dual Al2O3 MIS Gate Structure on DC and RF Characteristics of Enhancement-Mode GaN HEMT - Yuan Li; Yong Huang; Jing Li; Huiqing Sun; Zhiyou Guo (Micromachines)
A dual Al2O3 MIS gate structure is proposed to enhance the DC and RF performance of enhancement-mode GaN high-electron mobility transistors (HEMTs). As a result, the proposed MOS-HEMT with a dual recessed MIS gate structure offers 84% improvements in cutoff frequency (fT) and 92% improvements in maximum oscillation frequency (fmax) compared to conventional HEMTs (from 7.1 GHz to 13.1 GHz and 17.5 GHz to 33.6 GHz, respectively). As for direct-current characteristics, a remarkable reduction in off-state gate leakage current and a 26% enhancement in the maximum saturation drain current (from 519 mA·mm−1 to 658 A·mm−1) are manifested in HEMTs with new structures. The maximum transconductance (gm) is also raised from 209 mS·mm−1 to 246 mS·mm−1. Correspondingly, almost unchanged gate–source capacitance curves and gate–drain capacitance curves are also discussed to explain the electrical characteristic mechanism. These results indicate the superiority of using a dual Al2O3 MIS gate structure in GaN-based HEMTs to promote the RF and DC performance, providing a reference for further development in a miniwatt antenna amplifier and sub-6G frequencies of operation.